PENINGKATAN HASIL BELAJAR LOMPAT JAUH MELALUI PERMAINAN POS PATAHAN PADA SISWA KELAS V SD NEGERI BANTENG KECAMATAN TERSONO KABUPATEN BATANG TAHUN PELAJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study is to determine the improvement of student learning outcomes in the long jump learning through play post fracture in fifth grade elementary school Batang Bull. This study uses classroom action research. The design of classroom action research was conducted in two cycles with stages of planning, action, and reflection. The research subjects were students of class V Bull Elementary School District Tersono Batang. Data collection techniques using Penjasorkes assessment rubric, methods documentation,and questionnaires. The results showed that the fracture through the post game, the first cycle of student learning outcomes showed that 75% or 18 students achieve mastery learning and 25% or 6 students who have not achieved mastery learning, with. And student learning outcomes second cycle showed that 91.67% or 22 students achieve mastery learning and 8.33% or 2 students who have not achieved mastery learning. Because classical completeness percentage of student learning outcomes beyond 85%, the study of this class action has achieved success indicator. Conclusions from this research is learning through post game fracturing can improve learning outcomes student class V Bull Elementary School District Tersono Batang in the Academic Year 2012/2013.